1987
DOI: 10.1128/jb.169.11.5336-5338.1987
|View full text |Cite|
|
Sign up to set email alerts
|

Chemotaxis to plant phenolic inducers of virulence genes is constitutively expressed in the absence of the Ti plasmid in Agrobacterium tumefaciens

Abstract: The virulence (vir) genes are required in the early stages of plant tumor formation and are located together on the tumor-inducing (Ti) plasmid in Agrobacterium tumefaciens. Five of the vir genes are expressed inducibly in response to the following monocyclic phenolic compounds: acetosyringone, catechol, gallate, P-resorcylate, protocatechuate, p-hydroxybenzoate, and vanillin. Of these compQunds, only the latter five served as chemoattractants and only the latter three served as growth substrates for A. tumefa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
45
1
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(49 citation statements)
references
References 23 publications
2
45
1
1
Order By: Relevance
“…As described above, plants exude high levels of nutrients, and many of these act as chemoattractants for the bacteria. Different strains have been described to be positively chemotactic to sugars; amino acids; various dicarboxylic acids such as succinate, malate, fumarate; and aromatic compounds including shikimate, quinate, protocatechuate, vanillate, acetosyringone, gallate, catechol, and luteolin (15,34,62,201,371,372,414). One protein involved in sugar chemotaxis is ChvE of A. tumefaciens (Table 1), which is a chromosomally encoded sugar binding protein located in the periplasmic space (63).…”
Section: Chemotaxis Toward Plant Root Exudatesmentioning
confidence: 99%
“…As described above, plants exude high levels of nutrients, and many of these act as chemoattractants for the bacteria. Different strains have been described to be positively chemotactic to sugars; amino acids; various dicarboxylic acids such as succinate, malate, fumarate; and aromatic compounds including shikimate, quinate, protocatechuate, vanillate, acetosyringone, gallate, catechol, and luteolin (15,34,62,201,371,372,414). One protein involved in sugar chemotaxis is ChvE of A. tumefaciens (Table 1), which is a chromosomally encoded sugar binding protein located in the periplasmic space (63).…”
Section: Chemotaxis Toward Plant Root Exudatesmentioning
confidence: 99%
“…Chemotaxis and transport are two physiological functions that operate in this capacity, and a number of studies have shown that aromatic acids such as benzoate and 4-hydroxybenzoate are strong chemoattractants for Pseudomonas putida, as well as a number of other species of gram-negative bacteria including Agrobacterium spp. and rhizobia (19,20,31,39,40). However, very little is known about the characteristics of the presumed receptor proteins that are responsible for initial attractant recognition.…”
mentioning
confidence: 99%
“…These results indicated that the motility and chemotaxis are critical to A. tumefaciens infection under natural conditions (Hawes & Smith, 1989). Wild-type A. tumefaciens strains both containing and lacking Ti plasmid exhibited chemotaxis toward excised root tips from all plant species tested and toward root cap cells of pea and maize, suggesting that the majority of chemotactic responses in A. tumefaciens appear to be chromosomally encoded (Loake et al, 1988;Parke et al, 1987). However, the chemotactic response to some phenolic compounds, for example acetosyringone, which were identified as strong vir gene inducers, is controversial.…”
Section: Contact Ofmentioning
confidence: 83%